VARIATIONS AUTOUR DE LA « GIRLKULTUR » DANS THEA, BANDE DESSINÉE PARUE DANS "DAS HEFT. DIE NEUE ILLUSTRIERTE FRAUENZEITUNG" (1929-31) - DALLET-MANN, Véronique (Studia Universitatis Babeș-Bolyai Philologia, 2017)
Variations on the « Girl Culture » in Thea, Comic Strip Published in Das Heft. Die neue illustrierte Frauenzeitung (1929-31). The thirst for life characteristic of the 1920’s combines itself with the general acceleration of urban life to favour the emergence of new models of feminity in keeping with the conquest of the public space by a new generation, that of the « Girl ». The diverse manifestations of « Girl culture » give rise to multiple mediations and cultural transfers. A close reading of Thea, a comic strip designed by Chic Young and adapted into German by Richard Hutter, shows how signs of modernity are overturned and instrumentalised for the purpose of (re)domesticating women. Furthermore, the comic strip lends itself to questioning the effects of a media overexposure that favours the rise of an antifeminist ideology and the emergence of the essentialist model of the « German Woman ». REZUMAT. Variații referitoare la conceptul Girlkultur în Thea. Banda desenată publicată în Das Heft. Die neue illustrierte Frauenzeitung (1929-31). Setea de viață caracteristică anilor 1920 se îmbină cu accelerarea generală a vieții urbane pentru a favoriza apariția unor noi modele de feminitate, în concordanță cu cucerirea spațiului public de către o nouă generație desemnată în engleză prin «Girl». Diversele manifestării ale « Girlkultur » fac obiectul unor medieri și ale multiplelor transferuri culturale. Astfel, Thea, bandă desenată de Chic Young, adaptată în germană de Richard Hutter, arată cum semnele modernității sunt răsturnate și instrumentalizate în scopul unei (re)domesticiri a femeilor. În plus, benzile desenate tind să genereze o interogație cu privire la efectele unei supraexpuneri mediatice, care favorizează creșterea unei ideologii antifeministe și apariția modelului esențial al „femeii germane”. Cuvinte cheie: Republica de la Weimar, emanciparea femeilor, « Girlkultur », bandă desenată, transfer cultural